Traditional medicinal plants used in the treatment of tuberculosis in Ethiopia: A systematic review. Issue 5 (May 2022) - Getachew, Samuel; Medhin, Girmay; Asres, Abyot; Abebe, Gemeda; Ameni, Gobena
Abstract: Background: Majority of people in Ethiopia heavily rely on traditional medicinal plants to treat a number of diseases including tuberculosis (TB). However, there has been lack of comprehensive evidences on taxonomic distribution of medicinal plant species, methods of preparation of remedies from these plants and how the remedies are administered. This systematic review is designed to examine and synthesize available evidences focusing on medicinal plants that have been used for TB treatment in Ethiopia. Methods: Research findings related to ethno-botanical and pharmacological approaches of TB remedies were retrieved from databases. Electronic libraries of Ethiopian Universities and relevant church-based religious books were also reviewed as additional sources. Evidences are searched and organized in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. Result: From a total of 68 research documents that reported use of plants for treatment of TB 98 plants species belonging to 82 genera and 49 families were identified. The most frequently reported plant species belonged to family Lamiaceae (n = 8), Euphorbiaceae (n = 7), Cucurbitaceae (n = 6) and Fabaceae (n = 6). Croton macrostachyus, Allium sativum, and Myrsine Africana were the most often mentioned anti-TB medicinal plants. Shrubs (35.7%) and trees (29.6%) were reported as dominant growth forms while plant roots (31.6%) and leaves (28.6%) were frequently used plant parts for the preparations of the treatment. The most favored administration route was oral (59.1%). About 87% of the preparations were made from fresh plant materials. No experimental/clinical evidence was presented for 79.6%(78/98) of the reported plants to support their anti-mycobacterial activities. Conclusion: In Ethiopia, the number of herbal remedies is enormous and their use for TB treatment is a common practice. However, majority of them are not yet backed up by evidence generated through scientific experimentation and this warrants further experimental and clinical validations. Moreover, the efficacy, toxicity and safety tests should be initiated and this would help in the rapid identification of new anti-TB regimens, and possibly it would lead to developing more effective new plant-based drugs. This systematic review will serve as a reference for the selection of plants for developing new anti-TB regimens. Abstract : Medicinal plants, traditional, treatments, tuberculosis, Ethiopia.